Student Voices 3: Advocating for Global Health through Evidence, Insight and Action - Hoffman, Steven J. (My University, 2011)
This edited volume contains five essays written by students at McMaster University that were prepared for a fourth-year undergraduate course on Global Health Advocacy (HTH SCI 4ZZ3) that was taught by Steven Hoffman from January to April 2011 for the Bachelor of Health Sciences (Honours) Program in collaboration with the McMaster Health Forum. Through this publication, it is hoped that these students will help shape some of today’s leading debates in global health as they prepare themselves to confront tomorrow’s greatest challenges.
Keywords: student; global health; evidence; insight; action